The Unusual Presentation of Acute Pericarditis Mimicking Acute Coronary Syndrome - Intan, Ryan Enast; Octora, Tan Nicko; Alkaff, Firas Farisi; Balti, Dimas Rio (Biomolecular and Health Science Journal, 2019)
Pericarditis is a common disorder that might present in various settings, including primary-care and emergency department. However, the clinical features in some cases did not match with the written theory, which could lead to a misdiagnosis. A 46-year-old man presented to the emergency room with progressive tightness chest pain, epigastric pain, nausea, and vomiting in the past 2 days. Based on the clinical, electrocardiograph (ECG), and laboratory evaluation, the patient was diagnosed with unstable angina pectoris and treated accordingly but did not showed an improvement. Clinical re-examination and echocardiography evaluation showed a pathognomonic finding of pericarditis feature. Combination therapy of colchicine and ibuprofen was given for 3 weeks. One-month follow-up evaluation showed normal ECG and echocardiography result without any remaining symptoms. Acute pericarditis does not always show typical finding. Therefore, clinician must always aware with other differential diagnosis of chest pain and ECG variation of acute pericarditis.